Thermal Conductivity Enhancement of Hybrid Epoxy Composites Using Copper Oxide Nanoparticles and Carbon-Nanotubes - Abdullah, Laith; Al-hadithi, Mustafa; Faris, Abbas (Anbar Journal of Engineering Sciences, 2024)
In this current experimental research, the amount of improvement in the thermal conductivity of HEC hybrid epoxy resins was studied by adding copper oxide nanoparticles CuONp and carbon nanotubes (CNTs) as hybrid additives in different proportions to select the sample with the highest thermal conductivity value to include it in the design of the Flat Plate Solar Collector FPSC as Thermal Interface Material TIM reduces thermal resistance between the absorber plate and the tube. Four groups of samples were prepared using a mass balance with a sensitivity of 0.01g and a magnetic mixing device, then poured into cubic plastic molds to take the shape of the sample. The first group consists of one sample of pure epoxy to calibrate the thermal properties testing device through it. The second group consists of five samples of epoxy loaded with CNTs by weight (1, 3, 5, 7.5, 10) %. The third group consists of five samples of epoxy loaded with CuONp with weight percentages of (1, 3, 5, 7.5, 10) %. The fourth group consists of five samples of epoxy loaded with CuONp and CNTs combined in weight percentages of (1, 3, 5, 7.5, 10) %. The thermal conductivity of the samples was measured experimentally using the hot disk analyzer technique to measure thermal specifications. After comparing the thermal conductivity values of the samples, the highest value was 1.57 W/mK for the HEC sample loaded with 10% CNTs, which represents 9.23 times higher than pure epoxy